Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Our platform provides a seamless experience for finding precise answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the system of equations:
[tex]\[ y = 2x - 2 \][/tex]
[tex]\[ y = x^2 - x - 6 \][/tex]
we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here is a step-by-step solution:
1. Since both equations are equal to [tex]\(y\)[/tex], we set the expressions for [tex]\(y\)[/tex] equal to each other:
[tex]\[ 2x - 2 = x^2 - x - 6 \][/tex]
2. Rearrange the equation to form a standard quadratic equation:
[tex]\[ x^2 - x - 6 - 2x + 2 = 0 \][/tex]
[tex]\[ x^2 - 3x - 4 = 0 \][/tex]
3. Factor the quadratic equation:
[tex]\[ x^2 - 3x - 4 = (x - 4)(x + 1) = 0 \][/tex]
4. Set each factor equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x - 4 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
[tex]\[ x = 4 \quad \text{or} \quad x = -1 \][/tex]
5. Substitute these values of [tex]\(x\)[/tex] back into the first equation [tex]\( y = 2x - 2 \)[/tex] to find the corresponding [tex]\(y\)[/tex]-values:
For [tex]\(x = 4\)[/tex]:
[tex]\[ y = 2(4) - 2 = 8 - 2 = 6 \][/tex]
For [tex]\(x = -1\)[/tex]:
[tex]\[ y = 2(-1) - 2 = -2 - 2 = -4 \][/tex]
6. Therefore, the solutions to the system of equations are:
[tex]\[ (x, y) = (4, 6) \quad \text{and} \quad (-1, -4) \][/tex]
So the solutions to the system of equations are [tex]\((-1, -4)\)[/tex] and [tex]\( (4, 6)\)[/tex].
[tex]\[ y = 2x - 2 \][/tex]
[tex]\[ y = x^2 - x - 6 \][/tex]
we need to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex] that satisfy both equations simultaneously. Here is a step-by-step solution:
1. Since both equations are equal to [tex]\(y\)[/tex], we set the expressions for [tex]\(y\)[/tex] equal to each other:
[tex]\[ 2x - 2 = x^2 - x - 6 \][/tex]
2. Rearrange the equation to form a standard quadratic equation:
[tex]\[ x^2 - x - 6 - 2x + 2 = 0 \][/tex]
[tex]\[ x^2 - 3x - 4 = 0 \][/tex]
3. Factor the quadratic equation:
[tex]\[ x^2 - 3x - 4 = (x - 4)(x + 1) = 0 \][/tex]
4. Set each factor equal to zero and solve for [tex]\(x\)[/tex]:
[tex]\[ x - 4 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
[tex]\[ x = 4 \quad \text{or} \quad x = -1 \][/tex]
5. Substitute these values of [tex]\(x\)[/tex] back into the first equation [tex]\( y = 2x - 2 \)[/tex] to find the corresponding [tex]\(y\)[/tex]-values:
For [tex]\(x = 4\)[/tex]:
[tex]\[ y = 2(4) - 2 = 8 - 2 = 6 \][/tex]
For [tex]\(x = -1\)[/tex]:
[tex]\[ y = 2(-1) - 2 = -2 - 2 = -4 \][/tex]
6. Therefore, the solutions to the system of equations are:
[tex]\[ (x, y) = (4, 6) \quad \text{and} \quad (-1, -4) \][/tex]
So the solutions to the system of equations are [tex]\((-1, -4)\)[/tex] and [tex]\( (4, 6)\)[/tex].
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.